Tunable Multiwavelength Erbium-Doped Fiber Laser Employing PM-FBG and Mach–Zehnder Interferometer with Optical Fiber Delay Line - Wei He; Da Li; Lianqing Zhu; Mingli Dong; Fei Luo (IEEE Photonics Journal)
We propose the use of an erbium-doped fiber laser based on a polarization-maintaining fiber Bragg grating (PM-FBG) and all-fiber Mach–Zehnder interferometer (MZI) to realize a quadruple-wavelength 1.5-μm laser output. In the proposed system configuration, a 1535-nm center wavelength PM-FBG acts as the wavelength selector. The dual-pass MZI is fabricated using two couplers with a 50:50 splitting ratio, and the wavelength spacing of the comb is varied by using a spectrum power-driven optical fiber delay line inserted in MZI. The working threshold in the experiment is 82 mW. Tunable lasers of single-, dual-, triple-, and quadruple-wavelengths can be realized by adjusting the polarization controller. The generated wavelengths are in the range of 1534 to 1534.6 nm, the wavelength space is 0.2 nm, and the 3 dB linewidth is less than 0.05 nm. The power fluctuation is observed to be less than 0.912 dB, and the signal-to-noise ratio (SNR) is larger than 34.9 dB at 26 °C over a scan time of 10 min.